"It's classy because you can't see things": data from a project co-creating sexy images of young women. Issue 3 (3rd April 2022) - Phillips, Emma
ABSTRACT: Public and academic debates about sexualisation suggest that selfies taken by women of their own bodies, for display on Instagram, are sexualising and harming them. This paper reports on a "compare and contrast" project where a professional photographer (myself) took photographs of women who are sexy self-representers on Instagram. It is an examination of the aesthetics and practices of amateur and professional photography in this context, and draws attention to the role of class in making aesthetic judgements about women's sexy selfies. I argue that these respective photographic regimes produce and affirm their own sets of values which reveal the hierarchical and prejudiced nature of visual (and wider) culture as it relates to representations of women's bodies. I report on the verbal and visual languages used by participants and myself to make visible differing classed standards, through the concepts of what is "tasteful" and what is "vulgar". Dominant discourses about sexualised self-representations of women that focus on risks to the selfie-taker mask prejudices regarding class. The privileging of professional or "high art" aesthetics over amateur, "everyday aesthetics" perpetuates a policing and marginalising of women's bodies and sexualities and helps maintain long-standing ideals of female respectability and sexual decorum.